2022
DOI: 10.1371/journal.pone.0277134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neurogenic differentiation of human dental pulp stem cells

Abstract: Human dental pulp stem cells (hDPSCs) have increasingly gained interest as a potential therapy for nerve regeneration in medicine and dentistry, however their neurogenic potential remains a matter of debate. This study aimed to characterize hDPSC neuronal differentiation in comparison with the human SH-SY5Y neuronal stem cell differentiation model. Both hDPSCs and SH-SY5Y could be differentiated to generate typical neuronal-like cells following sequential treatment with all-trans retinoic acid (ATRA) and brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 145 publications
(178 reference statements)
0
11
0
Order By: Relevance
“…4F). To further identify axons, we examined the immunofluorescence staining of the neuron marker TUBB3 ( 73 , 74 ) and sensory neural marker Brn3a. We found that both markers were almost absent in the control NPCs but were strongly expressed by the iPSC-derived nociceptor-like sensory neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4F). To further identify axons, we examined the immunofluorescence staining of the neuron marker TUBB3 ( 73 , 74 ) and sensory neural marker Brn3a. We found that both markers were almost absent in the control NPCs but were strongly expressed by the iPSC-derived nociceptor-like sensory neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the immunofluorescence staining of neuron marker TUBB3 ( 62, 63 ) and sensory neural marker Brn3a. We found that both markers were almost absent in the nsNPCs but were strongly expressed by the iNOCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although DP-SCs are very similar to mesenchymal stem cells, they differ from them by their expression of neuronal specific markers (10). Interestingly, the Ocrelizumab positively affect the neuronal differentiation as it was for the osteogenic and chondrogenic differentiations.In DP-SCs, it was shown that ERK/MAPK is necessary for neuronal differentiation (16). In another study, the MAPK and TGF-β signaling pathways were shown to play a central role in the neurogenic differentiation, and the difference in those pathways between the DP-SCs and MSCs make DP-SCs more potential to differentiate neuron-like cells (17).The enhanced MAPK and TGF-β signaling in DP-SCs might be the reason for being the target of Ocrelizumab.…”
Section: Discussionmentioning
confidence: 99%